Autogenous shrinkage of alkali activated slag mortars: Basic mechanisms and mitigation methods. (July 2018) - Ballekere Kumarappa, Darshan; Peethamparan, Sulapha; Ngami, Margueritte
Abstract: This paper presents various mechanisms that can explain the cause of excessive autogenous shrinkage exhibited by alkali activated slag mortars (AASM) compared to Portland cement mortars (OPC). The influence of activator concentration parameters such as Na2 O content and of the silica modulus (Ms) on the magnitude of autogenous shrinkage are evaluated, as are the proposed mechanisms. The results show that the shrinkage kinetics of AASM is strongly dependent upon the rate of reaction, internal relative humidity (RH) and surface tension of the pore solution. Pore size variation between AASM and OPC mortars and the corresponding tensile stresses based on the capillary tension approach were also calculated using experimentally measured internal RH and surface tension values. A higher amount of both Na2 O and Ms. resulted in larger capillary stress resulting in greater autogenous shrinkage. Use of internal curing and of shrinkage reducing admixture were very effective in reducing the autogenous shrinkage of AASMs.